2015
DOI: 10.1093/mnras/stv732
|View full text |Cite
|
Sign up to set email alerts
|

Infall motions in massive star-forming regions: results from years 1 and 2 of the MALT90 survey

Abstract: Massive star-forming regions with observed infall motions are good sites for studying the birth of massive stars. In this paper, 405 compact sources have been extracted from the APEX Telescope Large Area Survey of the Galaxy (ATLASGAL) compact sources that also have been observed in the Millimetre Astronomy Legacy Team 90 GHz (MALT90) survey during Years 1 and 2. These observations are complemented with Spitzer GLIMPSE/MIPSGAL mid-IR survey data to help classify the elected starforming clumps into three evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 54 publications
5
73
3
Order By: Relevance
“…The infall velocity, V inf and the mass infall rate are estimated to be 1.8 km s −1 and 9.9×10 −3 M yr −1 , respectively. The mass infall rate estimate is higher compared to the value of 6.4 × 10 −3 M yr −1 derived by He et al (2015). As discussed in Section 3.3.4, our clump mass and radius estimates are higher.…”
Section: Infall Activitycontrasting
confidence: 63%
See 1 more Smart Citation
“…The infall velocity, V inf and the mass infall rate are estimated to be 1.8 km s −1 and 9.9×10 −3 M yr −1 , respectively. The mass infall rate estimate is higher compared to the value of 6.4 × 10 −3 M yr −1 derived by He et al (2015). As discussed in Section 3.3.4, our clump mass and radius estimates are higher.…”
Section: Infall Activitycontrasting
confidence: 63%
“…The clump enclosing G12.42+0.50, C1 is the largest and most massive clump having a radius 0.8 pc, column density 3.3×10 22 cm −2 and mass 1375 M . He et al (2015) derives the radius, column density and mass of the clump associated with G12.42+0.50 to be 0.57 pc, 1.3×10 23 cm −2 and 724 M , respectively. Apart from a larger size estimated by us, the other factors contributing to this difference in the estimated values of mass and column density are the different opacity and dust temperature values adopted by He et al (2015).…”
Section: Properties Of Cold Dust Clumpsmentioning
confidence: 99%
“…Contreras et al (2013), we found eight dense clumps involved in this region. Half of these (AGAL341.217-00.212, AGAL341.219-00.259, AGAL341.236-00.271, and AGAL341.266-00.302) show infall motions (He et al 2015), indicating star formation activities are ongoing actively in this filamentary cloud. We consider the mass-size relationship of these clumps to find out whether they have sufficient mass to form massive stars.…”
Section: Fragmentationmentioning
confidence: 98%
“…We assumed a cloud size of ∼1 pc (e.g. Dunham et al 2010Dunham et al , 2011Rosolowsky et al 2010;Urquhart et al 2014;He et al 2015;Wienen et al 2015;König et al 2017;Yuan et al 2017), a velocity gradient dv/dr = 1 km s…”
Section: Non-thermal Velocity Dispersion-temperature Relationmentioning
confidence: 99%